Linguaggi e ideologie del Rinascimento monarchico aragonese (1442-1503): Forme della legittimazione e sistemi di governo Languages and Ideologies of the Aragonese Monarchical Renaissance (1442-1503): Forms of Legitimacy and Systems of Government - Fulvio Delle Donne (Regna: Testi e studi su istituzioni, cultura e memoria del Mezzogiorno medievale, 2018)
The book focuses on the particular historical-political context of the Kingdom of Naples in the Aragonese period (1442-1503), and explores the variety of languages related to political practice: juridical, literary, artistic, political languages are analyzed in their specificities, but also in their reciprocal osmotic relations. This volume offers a conclusive reflection after a conference organized in Naples, and integrates interdisciplinary perspectives. It tests and refines the hypothesis concerning the gradual development of a complex organism that - through literature, oratory, political treatises, artistic representations and administrative practices - goes in the direction of a "state system", which still operates under the guidance of sovereignty.